Meningkatkan Efisiensi Penatausahaan Belanja Daerah di Kabupaten Pangkajene Kepulauan - Dharsana, Muhammad Try; Nirwana, Nirwana; Mediaty, Mediaty; Rasyid, Syarifuddin; Rura, Yohanis; Nagu, Nadhirah; Mahyuddin, Nurul Izzah; Syarif, Muh. Nur Irfan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: This community service activity aims to improve the ability of revenue treasurers to manage regional expenditure in Pangkep Regency. Methodology/approach: The research method used in the implementation of this community service activity is the primary approach. This approach allows active cooperation between the service team and the parties involved, such as the revenue treasurer and local government, in designing, implementing, and evaluating the changes needed in local financial management. Results/findings: The outcomes of this service activity clearly showed a significant improvement in the treasurer's ability to manage local finances, as well as the overall local financial management process. Limitation: The research steps, including Initial Assessment, Joint Planning, Action Implementation, Monitoring and Evaluation, Reflection and Improvement, and Dissemination of Results, helped ensure the success of this program. Contribution: This activity provides recommendations that have the potential to maintain and improve the ability of revenue treasurers in the future, with benefits that include increased efficiency and transparency in local financial governance, as well as more optimal contribution to the goal of practical regional autonomy.